PENGGUNAAN VIRTUAL REALITY UNTUK MELATIH PEMANDU WISATA GUNUNG MENANGANI PERTOLONGAN PERTAMA PADA KECELAKAAN DI ATAS GUNUNG - Parung, Joniarto; Ikawaty, Risma; Untung, Jimmy (Universitas Mataram, 2024)
Mountain climbing is a popular activityinspite of the high risk of accidents such as serious injuries and even death. In the event of an accident, mountain tour guides are often the first to deal with victims Therefore, performing first aid is a compulsory skill for a montain tour guide. In Indonesia, performing first aid is part of the national standard for working competency for mountain tour guides. The Community Service Program (PKM) from the University of Surabaya (Ubaya) aims to improve the skills of mountain tour guides in performing first aid. We considered training with VR as more efficient as it allows simulation of dangerous conditions on the mountain without risk to training participants and can be accessed at any time. We used a qualitative approach that begins with identifying the skills needed, preparing training substances, taking videos , video editing, training and evaluation. The outcome of this PKM is improvement in the skills of mountain guides in P3K which is expected to mitigate the risk of fatalities for mountain climbers who experienced accidents. Training and evaluation prove that training with VR is effective in improving accident handling competencies, providing a sustainable solution for repeated training for guides with limited time constraints.